How Single Is "Single" - Some Pragmatic Reflections on Single Versus Multifaceted Interventions to Facilitate Implementation; Comment on "Translating Evidence Into Healthcare Policy and Practice: Single Versus Multifaceted Implementation Strategies - Is There a Simple Answer to a Complex Question?" - Ann Catrine Eldh; Lars Wallin (Kerman University of Medical Sciences, 2015)
An earlier overview of systematic reviews and a subsequent editorial on single-component versus multifaceted interventions to promote knowledge translation (KT) highlight complex issues in implementation science. In this supplemented commentary, further aspects are in focus; we propose examples from (KT) studies probing the issue of single interventions. A main point is that defining what is a single and what is a multifaceted intervention can be ambiguous, depending on how the intervention is conceived. Further, we suggest additional perspectives in terms of strategies to facilitate implementation. More specifically, we argue for a need to depict not only what activities are done in implementation interventions, but to unpack functions in particular contexts, in order to support the progress of implementation science.